A mechanism for freshening the Caribbean Sea in pre‐Ice Age time. (11th June 2014) - Mestas‐Nuñez, Alberto M.; Molnar, Peter
Abstract Many believe that the Central American Seaway closed near 4 Ma and that that closure led to increased salinity in the Caribbean Sea and stronger Meridional Overturning Circulation in the Atlantic, which facilitated the waxing and waning of ice sheets in the Northern Hemisphere. We offer an alternative explanation for Caribbean salinification. The atmosphere transports approximately 0.23 Sv (1 Sv = 106 m3s−1) of fresh water (moisture) from the Caribbean to the Pacific today, but that amount varies by >20% during El Niño–Southern Oscillation events. Regressions of moisture transport against the Niño‐3 index, a measure of the sea surface temperature in the eastern tropical Pacific, show less moisture transport from the Caribbean during El Niño events than average. Abundant evidence indicates that at 3–4 Ma the eastern tropical Pacific was 3.5–4°C warmer than today, and if so, an extrapolation of such regressions suggests that smaller moisture transport across Central America might account for paleoceanographic inferences of a smaller salinity difference between the Caribbean and Pacific at that time. Accordingly, that decreased salinity difference at 3–4 Ma would not require blockage of relatively fresh Pacific water at 2–4 Ma by the closure of the Central American Seaway, but rather would be consistent with a transition from El Niño to La Niña‐like conditions in the eastern tropical Pacific around that time.